PENGARUH JUMLAH KUNJUNGAN WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN MOJOKERTO TAHUN 2006-2013 - NOVI DWI PURWANTI (Jurnal Pendidikan Ekonomi (JUPE), 2014)
The tourism sector is a potential sector to be developed as a source of local revenue. As a source of revenue receipts, tourism is affected by the number of tourists. Advancement of the tourism sector in a region very dependent for the number of tourists visiting. The tourist arrivals will bring revenue to the area he visited. This study has the objective to determine the effect of number of tourist visits to local revenues Mojokerto regency. This study uses the correlational research methods and quantitative approach and data analysis used in this study is a simple regression analysis. The conclusion of the study is the number of tourist arrivals has no effect on local revenues in Mojokerto. To make the number of tourist arrivals to be increase, the government needs to expand tourism activities such as entertainment, sports, camp and competitions to make the number of tourists so that would increase tourism levy and increase revenue Mojokerto. Keywords: tourism visit, revenue of area